2020
DOI: 10.37256/nat.112020121.26-37
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Self-cleaning Surfaces in Nature

Selim Mohammed S.

Abstract: A global interest was awarded to study the natural superhydrophobic surfaces since the description of the Lotus Effect by Barthlott and Neinhuis in 1997. Natural biomimetic surface merits of micro/nano-roughness, water contact ˃ 150°, sliding angles ˂10°, and minimized free-energy characteristics would motivate the dynamic fabrication of superhydrophobic surfaces. This critical review introduces an architectural panorama of numerous structural designs of natural superhydrophobic surfaces. Also, it discussed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
2
0
2
Order By: Relevance
“…Nature has always inspired mankind through billions of years of evolution. Various surfaces found in nature are superhydrophobic, such as butterfly wings, ,, water strider legs, , and canna and taro leaves . Pauli, the Nobel Prize winner in physics in 1945, said, ″God made solids, but surfaces were the work of the devil.″ These superhydrophobic, low-adhesion surfaces exhibit self-cleaning properties by allowing water to roll off easily and freely.…”
Section: Methodsmentioning
confidence: 99%
“…Nature has always inspired mankind through billions of years of evolution. Various surfaces found in nature are superhydrophobic, such as butterfly wings, ,, water strider legs, , and canna and taro leaves . Pauli, the Nobel Prize winner in physics in 1945, said, ″God made solids, but surfaces were the work of the devil.″ These superhydrophobic, low-adhesion surfaces exhibit self-cleaning properties by allowing water to roll off easily and freely.…”
Section: Methodsmentioning
confidence: 99%
“…Kemampuan superhidrofobik yang dimiliki lebih stabil dibandingkan dengan tanaman lain ditunjukkan dengan nilai sudut kontak air sebesar 160°. Selain nilai sudut kontak air, adapun beberapa faktor yang menjadi pendukung dalam kemampuan superhidrofobiknya diantaranya, bentuk mikrostruktur epidermis, kristal lilin epikutikular nanoskopik dari daun, dan stabilitas superhidrofobik di bawah kondisi kondensasi lembab (Mohammed S., 2020). Sifat superhidrofobik daun Teratai dalam kemampuan self-cleaning disebut sebagai "Lotus effect" dimana sebutan ini digunakan untuk menggambarkan sifat permukaan analog yang ditunjukkan oleh bahan sintetis.…”
Section: Daun Lotusunclassified
“…Sayap kupu-kupu memiliki permukaan kasar sehingga dapat bersifat hidrofobik dan dapat meningkatkan kemampuan self-cleaning, selain itu memiliki arah adhesi radial keluar ditunjukkan pada SEM sayap kupu-kupu pada Gambar 2(b) (Mohammed S., 2020). Kemampuan self-cleaning yang dimiliki karena permukaannya anisotropik yang menyebabkan sayapnya bebas kotoran secara alami.…”
Section: Sayap Kupu-kupuunclassified
“…Oil-infused surfaces have been demonstrated to withstand drop impact pressures of up to 680 atm . Textured oil-impregnated surfaces are also self-cleaning and omniphobic; that is, they repel a variety of fluids including low-surface-tension liquids (e.g., hexane and other organic liquids) and complex liquids (e.g., blood). , Although past studies have demonstrated the potential of lubricant-impregnated surfaces for enhancing various applications, including biofouling prevention, , drag reduction, , and increased heat transfer rate in condensation , and water harvesting, , currently these surfaces are not used in real-world applications due to the concern of shear-induced oil depletion. …”
mentioning
confidence: 99%